2019
DOI: 10.1016/j.jimonfin.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The term structure of exchange rate predictability: Commonality, scapegoat, and disagreement

Abstract: In this paper we study the exchange rate predictability across a range of investment horizons by proposing a generalized (term structure) model to capture the risk premium component of exchange rates with a broad set of variables meanwhile handle both parameter and model uncertainty. We demonstrate the existence of time-varying term-structural effect and model disagreement effect of exchange rate predictors as well as the projections of predictive information over the term structure. We further utilize the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 154 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…By comparing a portfolio based on expectations with trend and carry trade portfolios, it is found that carry trade strategies become less profitable with low interest rate differentials and note that the time-varying characteristic of monetary policy affects expectations [57]. The investigations show that currency carry trade risk premia and the linkage between carry trade risk premia and customer order flow could explain most of the term structure of exchange rate predictability [12]. Consistent with the literature on nonlinear exchange rate models, the excess returns with carry trading strategies, along with the potential asymmetric dependence between the carry trade and currency return, have been found in the foreign exchange market [58][59][60].…”
Section: Heterogeneous Agentsmentioning
confidence: 91%
See 2 more Smart Citations
“…By comparing a portfolio based on expectations with trend and carry trade portfolios, it is found that carry trade strategies become less profitable with low interest rate differentials and note that the time-varying characteristic of monetary policy affects expectations [57]. The investigations show that currency carry trade risk premia and the linkage between carry trade risk premia and customer order flow could explain most of the term structure of exchange rate predictability [12]. Consistent with the literature on nonlinear exchange rate models, the excess returns with carry trading strategies, along with the potential asymmetric dependence between the carry trade and currency return, have been found in the foreign exchange market [58][59][60].…”
Section: Heterogeneous Agentsmentioning
confidence: 91%
“…Higher implementation costs lead to higher volatility and risk, so carry traders will not be active in the market [78]. Only if the carry trade strategy is expected to be profitable will it be implemented, and then the weights of different types of forecasting rules would be the upper parts of Equations (12) and (13). If r d t − r f t is lower than the threshold τ, then the carry trade strategy will not yield substantial profit, and carry traders will disappear from the market.…”
Section: Switching Mechanism For Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capistrán and Timmermann () talk about long‐ and short‐term forecast disagreements in the context of inflation. Cao et al () propose a generalized term structure model for exchange rate predictability across different investment horizons.…”
Section: Disagreement Volume and Treasury Futuresmentioning
confidence: 99%
“…More recently, this line of literature has been growingly rich in emphasizing the term structure of disagreements. To date, the role of disagreement at different maturities has been discussed in the context of federal funds rates and GDP output (Andrade, Crump, Eusepi, & Moench, 2016), inflation (Andrade et al, 2016;Capistrán & Timmermann, 2009), bond yields (Crump, Eusepi, & Moench, 2018), and exchange rates (Cao, Huang, Liu, & MacDonald, 2018). Evident from these studies, disagreements in the short-and long-term segments of a market are economically different.…”
Section: Introductionmentioning
confidence: 99%